Analysis of energy gradients and sediment loads occurring in the Irish Creek Watershed located in northeast Kansas - Sullivan, Justine Danielle (Kansas State University, 2013)
Sediment is a large pollutant concern for the United States and is a major impairment source in water bodies (MARC 2013). Rivers and streams assessed in Kansas resulted in 87.8% being considered impaired, as well as 97.8% of the assessed lakes, reservoirs, and ponds (EPA 2012d). Tuttle Creek Reservoir is filling with sediment faster than any other federal reservoir in the region. Due to the importance of Tuttle Creek Reservoir, limiting the water impairments has been made a priority. The tributaries feeding the reservoir are all considered impaired, and TMDLs should be developed to limit the amount of sediment allowed in the water body. This study focuses on the stream energy and sediment loads occurring in a watershed in northeast Kansas over a six year period. When bankfull conditions occur, significant amounts of work are performed on the stream and excessive erosive forces may occur. The estimated bankfull discharge was 6.5 m3/s, and this event occurred every year except in 2012. At the same location the bankfull discharge was estimated, automated and grab water samples were collected and stream power was calculated. The samples were analyzed for total suspended sediment, total nitrogen, and total phosphorus, and the total annual loads were estimated. The total sediment load occurring in the watershed was 10,298,283 kilograms. The nutrient loads occurring were 78,213 kg of TN and 22,625 kg TP. Elevations were measured at equal intervals in a sub-watershed. Energy gradients were calculated, and it was observed that many of the gradients could create favorable conditions for sediment erosion to occur. The stream power estimate was 26.85 kg/m/s. At this stage larger sediment particles and load could be transported. A gully formed by overland flow entering the stream was also measured to estimate amounts of sediment being contributed from gully side conveyances within the watershed. The estimated sediment loss from the gully was 1,693,899 kg. Results of this study could help improve water quality and help quantify the amount of sediment being carried from the watershed and streambanks, so BMPs and other design features may be implemented.
Keywords: Energy gradients; Sediment; Erosion; Nutrients; Discharge; Water quality; Engineering, Agricultural (0539); Environmental Engineering (0775)